$$φ $$ ϕ meson mass and decay width in magnetized strange hadronic matter - Nisha Chahal; Rajesh Kumar; Suneel Dutt; Arvind Kumar (European Physical Journal C: Particles and Fields)
Abstract We investigate the medium modifications in mass and decay width of $$φ $$ ϕ meson in the presence of an external magnetic field. The in-medium mass of $$φ $$ ϕ meson has been calculated using the decay process $$φ $$ ϕ $$→ $$ → $$K {\bar{K}}$$ K K ¯ at one-loop level. The medium modifications are introduced by using a chiral SU(3) model employing a mean-field effective approach. Due to the introduction of the magnetic field, masses of charged $$K^+$$ K + and $$K^-$$ K - increases with advancing magnetic field values. A negligible change in the value of neutral $$K^0$$ K 0 and $${\bar{K}}^0$$ K ¯ 0 has been observed for varying magnetic fields. Due to electromagnetic interactions with charged K and $${\bar{K}}$$ K ¯ mesons, there is a gradual augmentation in the effective mass of $$φ $$ ϕ meson. The probability of the mentioned decay process ceases to be zero for low density and strangeness fraction values at higher magnetic field values. Investigating the decay width and effective mass of $$φ $$ ϕ meson under the influence of an external magnetic field is relevant to understanding the hadronic matter properties under extreme conditions achievable at heavy-ion collision experiments.